0
$\begingroup$

I'm reading the chapter "Homology" on Topology and Geometry by Bredon, and I tried to calculate the group $H_0(*)$ by the definition but I can't do it. Here's my attempt:

We shall calculate the $0$th homology group of the singleton $X=\{*\}$. Observe that there exists a single map $\sigma_0 \colon \Delta_0 \to X$. Hence the singular $0$-chain group $\Delta_0(X)$ is the group $\{0 \sigma_0, 1 \sigma_0, -1 \sigma_0,...\}$. The $0$th homology group of $\{*\}$ is $(\ker \partial_0)/(\mbox{im } \partial_{1})$. Note that $\partial_0 \colon \Delta_0(X) \to \Delta_{-1}(X)$, and, by definition, $\Delta_{-1}(X)=0$. Hence \begin{align*} \partial_0 \colon \Delta_0(X) &\to \Delta_{-1}(X) \\ n \sigma_0 &\mapsto 0, \end{align*} which implies $\ker \partial_0 = \Delta_0(X)$. Analogously there exists a single map $\sigma_1 \colon \Delta_1 \to X$. Hence $\Delta_1(X) = \{0 \sigma_1, 1 \sigma_1, -1 \sigma_1,...\}$. We have, by definition, \begin{align*} \partial_1 \colon \Delta_1(X) &\to \Delta_{0}(X) \\ n \sigma_1 &\mapsto n (\sigma_1 \circ F_0^1 - \sigma_1 \circ F_1^1). \end{align*} Since $X$ is a singleton, we have $\sigma_1 \circ F_0^1 - \sigma_1 \circ F_1^1 = \sigma_0$, which implies $\partial_1$ is a bijection, hence $\mbox{im } \partial_{1} = \Delta_0(X)$. Finally, we have $H_0(X)= \Delta_0(X)/ \Delta_0(X) \cong 0$.

I know that $H_0(X) \cong \mathbb{Z}$, but I don't understand the explanation given by Bredon.

$\endgroup$
1
  • $\begingroup$ What don't you understand? If you are more specific, we can help you. $\endgroup$ Jul 7 '17 at 17:34
2
$\begingroup$

$$\newcommand{\si}{\sigma}$$ You are right that $H_0(X)$ and $H_1(X)$ are free Abelian groups with generators $[\si_0]$ and $[\sigma_1]$ respectively (I prefer this notation with brackets). The error is that the boundary $\partial_1[\si_1]$ is not $[\si_0]$ as you have it, but is zero. Thus the cycle group is $Z_0=\Delta_0(X)=\Bbb Z[\si_0]$ and the boundary group is $B_0=0$. Then $H_0(X)=Z_0/B_0\cong\Bbb Z$.

$\endgroup$
3
  • $\begingroup$ I'm failing to see that $\partial_1 [\sigma_1]=0$. If $\partial_1 (n \sigma_1) = n \partial_1 ( \sigma_1)$ (by definition), then it can't "change" the coefficient $n$ to $0$, right? $\endgroup$ Jul 7 '17 at 18:12
  • $\begingroup$ @HilarioFernandes $\partial_1$ of a path is the difference between its endpoints considered as elements of $Z_0(X)$. In our example the path $\sigma_1$ has both endpoints the same, so $\partial_1[\sigma_1]=[\sigma_1]-[\sigma_1]=0$. $\endgroup$ Jul 7 '17 at 18:52
  • $\begingroup$ Oh, I see. By realizing that $\sigma_1 \circ F_0^1 = \sigma_0 = \sigma_1 \circ F_1^1$, we have $n(\sigma_1 \circ F_0^1 - \sigma_1 \circ F_1^1) = n(\sigma_0-\sigma_0)=(n-n)\sigma_0 = 0 \sigma_0$. $\endgroup$ Jul 7 '17 at 19:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.